An overview of the toll collection system of the Malaysian highway authority / Rozana Abdul Kadir - Abdul Kadir, Rozana (1988)
This project paper is prepared in partial fulfillment of the Advanced Diploma in Accountancy course. For this purpose, the writer has chosen a topic on 'An Overview of the Toll Collection System of the Malaysian Highway Authority. Toll collection has become one of the hot topics recently, among which many people are not happy in having to pay high tolls and in the introduction of the closed toll system along the Kuala Lumpur - Air Keroh expressway and the Ipoh - Changkat Jering expressway. These reasons have prompted the writer to study the operations of the toll collection systems.